Internet connectivity disruption in Iran (Iran) - Voidly (2026)
CRITICAL severity mixed detected in Iran. Confidence: 67%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: IR-2026-0170
Keywords: censorship; IR; mixed; critical